PSM/PTA asset management ystem (PAMS) - Nurul Hafizah, Johar (2013)
Asset management system is a system that manages asset information. The information of the asset is inserting into the system, updating and deleting by the person or group that in charge for the asset management. PSM/PTA Asset Management system (PAMS) is developed to ease the workload. The development process of PAMS is partitioned into phase such as planning, user design, construction and cutover, based on the Rapid Application Development (RAD) methodology. By implementing PAMS, the PSM/PTA asset and borrowing records were able to be dynamically updated and access by all parties at any time. For future enhancements, the notification is sent to the supervisor and technician when the borrow application is sent by student.